Becoming comfortable with the uncomfortable: The tale of adaptability - Anke van der Merwe; Roline Barnes; Mariette Nel (AOSIS, 2023)
Background: With the ever-changing healthcare environment and impact of the coronavirus disease 2019 (COVID-19) pandemic on tertiary education, healthcare students need to constantly adapt their approach to learning, clinical practice and well-being. Adaptive performance is therefore vital. Objectives: To investigate the adaptive performance of final year physiotherapy students at the University of the Free State. Method: A quantitative descriptive study was performed. All consenting final year undergraduate physiotherapy students registered at the University of the Free State in 2021 were approached for inclusion. The short 55-item I-ADAPT measurement was distributed electronically to all possible participants. Results: The response rate was 28.5% (n = 8). Descriptive statistics, namely frequencies and percentages for categorical data and medians and percentages for numerical data were calculated. The dimensions related to handling work stress (50%), uncertainty (62.2%) and creativity (64.0%) scored the lowest. Emotional response to stress (62.5%) and frustration in response to unpredictable situations (62.5%) was reported. Conclusion: Uncertainty and unpredictability are inevitable for healthcare students. Stress management and emotional intelligence development are advised for inclusion in undergraduate physiotherapy programmes. Clinical implications: A need for curricular evaluation to ensure students are equipped with stress management and emotional intelligence skills is proposed.